MEMELIHARA KEHIDUPAN: MENGINTERPRETASI HUKUM BUNGA PINJAMAN DALAM ULANGAN 23:19-20 DALAM KONTEKS D - Roy Charly Sipahutar (IAKN Ambon, 2021)
The starting point of this article is from the many social problems that arise from the practice of interest is completely uncontrolled. There are many impacts they pose, among others: the impoverishment and injustice. Various parties should be responsible instead tend not to care, even a fully devolved to the legal requirements prevailing market. Therefore, here I see the importance of a biblical basis that can later be used as a theological reference for market participants and churches in arranging this interest practices. Interpretation rational Socio-Historical approach for Deuteronomy 23: 19-20 (20-21) to find the deepest meaning of Scripture in regulating the practice of this kind, for the sake of a fair coexistence and peace. As such, it encourages every business person to engage in business within the legal and sovereignty of the country, and readers (or churches) are constantly reminded to encourage the nation and the church to organize its economic system that adheres to the basic principles of life preservation.